2003
DOI: 10.1046/j.1523-1755.2003.00035.x
|View full text |Cite
|
Sign up to set email alerts
|

Bone morphogenic protein-7 (BMP-7), a novel therapy for diabetic nephropathy11Professor Robert Chevalier served as a guest editor for this paper.

Abstract: BMP-7 partially reversed diabetic-induced kidney hypertrophy, restoring GFR, urine albumin excretion, and glomerular histology toward normal. Restoration of BMP-7 expression was associated with a successful repair reaction and a reversal of the ill-fated injury response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
59
1
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 213 publications
(63 citation statements)
references
References 33 publications
(21 reference statements)
1
59
1
2
Order By: Relevance
“…Its ongoing role in osteoblast function suggests a hormonal role, and circulating levels are detectable. BMP-7 expression is downregulated early in CRF (21)(22)(23), and the concept of CRF as a state of BMP-7 deficiency is supported by studies showing that therapy with BMP-7 is efficacious in several rodent models of renal disease (21,(23)(24)(25)(26)(27). BMP-7 may also play a role in maintaining VSMC differentiation and preventing transdifferentiation of VSMC into an osteoblast phenotype.…”
mentioning
confidence: 78%
“…Its ongoing role in osteoblast function suggests a hormonal role, and circulating levels are detectable. BMP-7 expression is downregulated early in CRF (21)(22)(23), and the concept of CRF as a state of BMP-7 deficiency is supported by studies showing that therapy with BMP-7 is efficacious in several rodent models of renal disease (21,(23)(24)(25)(26)(27). BMP-7 may also play a role in maintaining VSMC differentiation and preventing transdifferentiation of VSMC into an osteoblast phenotype.…”
mentioning
confidence: 78%
“…Antifibrotic action of BMP-7 is mediated via direct antagonism of TGF-␤1 signaling (12,28,29). Previous studies suggest a therapeutic benefit for rhBMP-7 in a rat model of STZ-induced diabetic glomerulosclerosis (which do not develop interstitial fibrosis) (30).…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies have shown that TGF-␤ is an important factor in diabetic nephropathy progression through the use of knockout (KO) mouse models for the TGF-␤ type II receptor (9) (which binds TGF-␤1) and TGF-␤ blocking antibodies (10 -12). The investigation of other molecules involved in the regulation of TGF-␤ such as the antifibrogenic peptide bone morphogenic protein 7 (BMP7) (13), which counterbalances TGF-␤ activity and is downregulated in diabetes (14), have also shown efficacy as a strategy for reducing diabetic nephropathy progression (15). Although TGF-␤ is involved in the onset and progression of diabetic nephropathy, the nature of this role, particularly related to the onset of albuminuria, remains speculative.…”
mentioning
confidence: 99%